Career-Personal Life Equilibrium in Academia: The Remote Workplace and Married Women Faculty in Higher Education (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Faculty, are currently being pressurised to do multiple work with an eye on garnering higher grades in the accreditation race. It may be a good initiative to fire on all fronts but what is glaring is the lacunae in faculty skills, infrastructure and the servicescape. The pandemic has compounded this problem given the fact that the workplace has shifted from campuses to homes. The current study endeavours to examine the impact that the workplace ambience has on work efficacy and career-personal life equilibrium. The impression of marital contentment is also investigated. Purposive sampling led to 443 filled-in and complete responses which were analysed.